Concrete pavement design, construction, and performance - Delatte, Norbert J. (A Spon Press book, 2014)
"This book addresses the design, construction, and performance of concrete pavements. It sets out best practices for the construction of economical, long life concrete pavement by engineers in the public and private sectors. It also outlines first alternatives for concrete pavement solutions, and identifies their performance and behavior parameters. The text addresses materials selection and mix design; as well as pavement construction. It emphasizes the coherence of these three elements: materials, design, and construction, and covers highways, airport, industrial, and light duty pavements"